Coexistence of Neuromyelitis Optica and Amyotrophic Lateral Sclerosis: A Case Report. (January 2019) - Li, Amy; McGranahan, Tresa; Su, Elaine; Kipp, Lucas; Gold, Carl A.
The occurrence of amyotrophic lateral sclerosis (ALS) and neuromyelitis optica (NMO) in a single patient is exceedingly rare. We report a case of a 54-year-old woman of East Asian descent with a prior diagnosis of ALS who developed an episode of unexplained hiccups and nausea and vomiting consistent with area postrema syndrome 3 months prior to the onset of acute transverse myelitis. Magnetic resonance imaging revealed abnormal T2 hyperintensity and gadolinium enhancement at the cervicomedullary junction with extension to C3. Imaging was also notable for nonenhancing central cord T2 hyperintensity from T6 to T8 suggesting previous demyelination. The patient's cerebrospinal fluid analysis was mildly inflammatory. She was found to have a positive NMO/aquaporin-4 immunoglobulin G titer (cell-based assay) greater than 1:100 000, consistent with a diagnosis of NMO. The unusual coexistence of ALS and NMO prompts consideration of potential common pathological neuroinflammatory processes.